2014
DOI: 10.1105/tpc.114.126573
|View full text |Cite
|
Sign up to set email alerts
|

LNK1 and LNK2 Are Transcriptional Coactivators in the Arabidopsis Circadian Oscillator

Abstract: Transcriptional feedback loops are central to the architecture of eukaryotic circadian clocks. Models of the Arabidopsis thaliana circadian clock have emphasized transcriptional repressors, but recently, Myb-like REVEILLE (RVE) transcription factors have been established as transcriptional activators of central clock components, including PSEUDO-RESPONSE REGULATOR5 (PRR5) and TIMING OF CAB EXPRESSION1 (TOC1). We show here that NIGHT LIGHT-INDUCIBLE AND CLOCK-REGULATED1 (LNK1) and LNK2, members of a small famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
171
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 159 publications
(185 citation statements)
references
References 62 publications
(92 reference statements)
10
171
2
2
Order By: Relevance
“…S5). The yeast two-hybrid screening is thus consistent with a previous report showing the rhythmic interaction of LNK1 and LNK2 with RVE8 and with RVE4 (21).…”
Section: Resultssupporting
confidence: 79%
See 4 more Smart Citations
“…S5). The yeast two-hybrid screening is thus consistent with a previous report showing the rhythmic interaction of LNK1 and LNK2 with RVE8 and with RVE4 (21).…”
Section: Resultssupporting
confidence: 79%
“…The fact that under LD cycles, the anthocyanin biosynthetic genes were up-regulated in both RVE8-ox and dm plants also suggests that RVE8 might act as an activator, whereas LNK1 and LNK2 might be repressors of the anthocyanin biosynthetic pathway. A previous report has demonstrated that LNK1 and LNK2 together with RVE4 and RVE8 act as transcriptional coactivators in the regulation of circadian gene expression (21). Our results open the interesting possibility that under LD cycles, the role of LNK-RVE8 interaction in the control of anthocyanin regulation might be opposed to that exerted on circadian core gene expression.…”
Section: Resultscontrasting
confidence: 43%
See 3 more Smart Citations